2020
DOI: 10.1186/s12955-020-01424-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life analysis of patients treated with cetuximab or cisplatin for locoregionally advanced squamous cell carcinoma of head and neck in the United States

Abstract: Background: To compare quality of life of patients treated with cetuximab with or without radiation therapy (±RT) vs. cisplatin±RT for locoregionally advanced squamous cell carcinoma of the head and neck (SCCHN) in the realworld setting. Methods: In this retrospective observational study, electronic medical records and Patient Care Monitor (PCM) survey data from the Vector Oncology Data Warehouse were utilized from adult patients in the United States who received initial treatment with cetuximab±RT or cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Ye et al. retrospectively analyzed a multi‐institutional cohort of 349 patients with head and neck cancer of all subsites treated with CRT with cisplatin or cetuximab and found grade 3/4 toxicities in 58% and 45% in each group, respectively, most commonly oral mucositis and radiation dermatitis, as well as a 34% and 20% rate of unplanned hospital admissions, respectively, consistent with other similar studies 2175,2176 . In an RCT by Bonner et al.…”
Section: Qol After Multimodality Treatment For Sinonasal Malignanciessupporting
confidence: 64%
“…Ye et al. retrospectively analyzed a multi‐institutional cohort of 349 patients with head and neck cancer of all subsites treated with CRT with cisplatin or cetuximab and found grade 3/4 toxicities in 58% and 45% in each group, respectively, most commonly oral mucositis and radiation dermatitis, as well as a 34% and 20% rate of unplanned hospital admissions, respectively, consistent with other similar studies 2175,2176 . In an RCT by Bonner et al.…”
Section: Qol After Multimodality Treatment For Sinonasal Malignanciessupporting
confidence: 64%
“…The initial intention of this study was to perform a meta-analysis of the QoL scores among patients undergoing HNC treatment with anti-EGFR inhibitors. This antineoplastic agent was chosen for its debilitating side effect profile [58][59][60]. It was found that studies utilizing the same assessment tools differed in their reporting methods, and this prevented doing a pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, cetuximab stands as the only molecularly targeted drug approved for HNSCC treatment 10 . Despite its potential therapeutic bene ts, the use of cetuximab in HNSCC patients can be associated with cutaneous toxicities that can limit treatment e cacy and patient quality of life 11 ; 12 . These adverse effects, typically manifesting as an acne-like rash, often affect the face, scalp, and neck regions and can lead to discomfort, pain, and reduced physical and social functioning.…”
Section: Introductionmentioning
confidence: 99%